The Effectiveness of Interpersonal Communication Through Coaching Method For Employee In RSUD R. Syamsudin, SH - Widiana Latifah; Nani Nurani Muksin (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
In the era of globalization marked by intense competition between hospitals, it is necessary to anticipate an increase in service quality on an ongoing basis in line with higher customer expectations for hospital services. Top management of RSUD R. Syamsudin, S.H. Sukabumi City has determined the policy of coaching method as a mean of interpersonal communication among the leader and staffs to increase the motivation and as part of the staff development efforts, since nowadays the hospital staffs are required to have high motivation to work to perform in health service. The purpose of this study was to determine how the effectiveness of interpersonal communication affects the success of the coaching method. This research was conducted using a qualitative descriptive method. Data were collected through in-depth interviews with two coaches and one coachee. The results showed that the effectiveness of interpersonal communication in the coaching method affected the success of the coaching process. Openness is marked by the coachee's willingness, to be honest, and open with the coach, empathy is carried out by active listening and clarifying, a supportive attitude is carried out through self-disclosure and powerful questions, a positive attitude is carried out by building trust and acceptance of positive thoughts and equality which is marked by eliminating the position subordinate superiors and the form of conversation in the form of dialogue and discussion.